Impact of polypyrrole incorporation on nickel oxide@multi walled carbon nanotube composite for application in supercapacitors. (September 2020) - Yadav, Hemraj M.; Ramesh, Sivalingam; Kumar, K. Ashok; Shinde, Surendra; Sandhu, Sanjay; Sivasamy, Arumugam; Shrestha, Nabeen K.; Kim, Heung Soo; Kim, Hyun-Seok; Bathula, Chinna
Abstract: In this article we report the synthesis of polypyrrole incorporated nickel oxide multi walled carbon nanotube (NiO@NMWCNT/PPy) composites by thermal reduction protocol for supercapacitor applications. The structural and morphological properties of the composites were confirmed by the aid of X-ray diffraction (XRD), Field-emission scanning electron microscope (FE-SEM) with energy-dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS) and Field-emission transmission electron microscopy (FE-TEM) analysis indicating the hexagonal crystal structure of NiO decorated on NMWCNT/Ppy. The electrochemical characteristics of the NiO@MWCNT/PPy composite were analyzed in the presence of 2 M KOH as an electrolyte. The NiO@NMWCNT/PPy nanostructured composite produced a plenty of active sites for ion migration reactions that facilitate the energy storage mechanism. As a proof of concept demonstration, the NiO@NMWCNT/PPy composite was explored as an electrode materials in supercapacitor and exhibited specific capacitance of 395 F g −1 and cyclic stability up to 5000 cycles at 0.5 A g −1 . Enhanced performance of composite is attributed to the incorporation of polypyrrole in NiO@NMWCNT. The improved capacitance and cyclic stability demonstrated by the composite indicates the NiO@NMWCNT/PPy to be a promising candidate for supercapacitor applications. Highlights: Synthesis of NiO@N-MWCNT/PPy composites by thermal reduction protocol. The structural and morphological properties were studied. Specific capacitance of 395 F g −1 and cyclic stability up to 5000 cycles at 0.5 A/g. Impact of polypyrrole incorporation of on NiO@N-MWCNT studied.